2019
DOI: 10.3390/toxins12010006
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Study of Cyanotoxins in Paleolimnological Research: Current Knowledge and Future Needs

Abstract: Cyanobacterial metabolites are increasingly studied, in regards to their biosynthesis, ecological role, toxicity, and potential biomedical applications. However, the history of cyanotoxins prior to the last few decades is virtually unknown. Only a few paleolimnological studies have been undertaken to date, and these have focused exclusively on microcystins and cylindrospermopsins, both successfully identified in lake sediments up to 200 and 4700 years old, respectively. In this paper, we review direct extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 108 publications
0
16
0
Order By: Relevance
“…Because of the potent toxicity, the International Agency for Research on Cancer (IARC) has categorized MC-LR as possibly carcinogenic to humans (Group 2B). And the guideline value set by the World Health Organization (WHO) for MC-LR in drinking water is 1 μg/L (11). So, the removal of MC-LR from drinking water resources is very necessary for human health and environmental safety (12).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the potent toxicity, the International Agency for Research on Cancer (IARC) has categorized MC-LR as possibly carcinogenic to humans (Group 2B). And the guideline value set by the World Health Organization (WHO) for MC-LR in drinking water is 1 μg/L (11). So, the removal of MC-LR from drinking water resources is very necessary for human health and environmental safety (12).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study based on meta-analysis approach showed that overall, N-rich toxin content in cyanoprokaryotes and dinoflagellate increased with P limitation, while it tended to decrease with N limitation [124]. Although the paleolimnological data on phycotoxins are quite scarce, similar results were obtained on correlation between N and P and MC content in sediments [99]. The role of trace metals, and especially the importance of zinc and iron-limited conditions for production of cyanotoxins (MCs), was also demonstrated [101,102,125].…”
Section: Phycotoxins and Factors That Affect Their Productionmentioning
confidence: 58%
“…Due to the combined effect of these functional bacteria, the MC concentration maintains at a relatively low level in the natural environment. However, Henao et al found MCs could be detected in sediment cores through paleolimnological investigations, indicating that these MC-degrading bacteria are unable to completely degrade all of toxins under environmental conditions [14]. The variability of natural climate may affect the degradation of MCs by functional bacteria in the natural environment.…”
Section: Discussionmentioning
confidence: 99%